1994
DOI: 10.3189/1994aog20-1-397-400
|View full text |Cite
|
Sign up to set email alerts
|

20th century behaviour of Drygalski Ice Tongue, Ross Sea, Antarctica

Abstract: ABSTRACT. Drygalski Ice Tongue is the floating seaward extension of DavidGlacier, a large outlet glacier draining from Talos and Circe Domes of the East Antarctic ice sheet. Several explorers mapped and described Drygalski Ice Tongue in the early years of the 20th century and, although this information does not allow detailed interpretation of ice-tongue behaviour, it is clear that from 1900-12 it was a significant feature extending 65-75 km from the coast. More detailed information has been compiled from aeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
(16 reference statements)
1
25
0
Order By: Relevance
“…They concluded on the basis of their analysis that the mean polynya area is 1300 km 2 (65 km north/south by 20 km east/west) but varied in size from near zero to 5000 km 2 (65 km north/south by 75 km east/west). This maximum polynya area corresponds roughly to a polynya with an offshore extent equal to the length of the Drygalski Ice Tongue (-83 km in 1979 [Frezzotti and Mabin, 1994]). Kurtz and Bromwich [1985] also noted that the open water nucleus was surrounded by -25,000 km 2 of thin or loosely consolidated ice.…”
Section: Ice Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded on the basis of their analysis that the mean polynya area is 1300 km 2 (65 km north/south by 20 km east/west) but varied in size from near zero to 5000 km 2 (65 km north/south by 75 km east/west). This maximum polynya area corresponds roughly to a polynya with an offshore extent equal to the length of the Drygalski Ice Tongue (-83 km in 1979 [Frezzotti and Mabin, 1994]). Kurtz and Bromwich [1985] also noted that the open water nucleus was surrounded by -25,000 km 2 of thin or loosely consolidated ice.…”
Section: Ice Conditionsmentioning
confidence: 99%
“…These studies indeed confirmed Priestly's earlier finding that open water exists throughout the winter months. Bromwich [1983, 1985] This maximum polynya area corresponds roughly to a polynya with an offshore extent equal to the length of the Drygalski Ice Tongue (-83 km in 1979 [Frezzotti and Mabin, 1994] …”
Section: Ice Conditionsmentioning
confidence: 99%
“…Radio-echo sounding profiles of B15A reported by Peters and others (2007;also J. Holt and D. Blankenship, personal communication, 2005; see also Bentley and others, 1979) suggest a range of thickness averaging $250 m. At the central AWS site on C16, the thickness was observed to be 144 AE 14 m using a hand-held spot radar. At several points along the edge, the thickness was as low as 26 AE 3 m. The thickness of the tip of the Drygalski Ice Tongue, from which iceberg C25 calved, was estimated to be 300 m based on reports of a recent remote-sensing survey (see Frezzotti and Mabin, 1994;Parmiggiani and Fragiacomo, 2005). Using 250, 100 and 300 m for the average thicknesses of icebergs B15A, C16 and C25, their areas measured from satellite imagery, and a density of 900 kg m -3 , the masses of the icebergs were estimated to be 2.7 Â 10 15 , 6.5 Â 10 14 and 9.7 Â 10 13 kg, respectively.…”
Section: Forces Of Iceberg Collisionsmentioning
confidence: 99%
“…The forcing of C25 appears to be more noisy than that of C16, and this may reflect the fact that C25 was scraping past the ice tongue, while C16 was separated from the ice tongue by virtue of the intervening presence of C25. C16 is also less thick than C25 (estimated to be $300 m; Frezzotti and Mabin, 1994;Parmiggiani and Fragiacomo, 2005), so edge-on-edge scraping against the Drygalski Ice Tongue would be less effective in restraining C16's motion than it would be in restraining that of C25.…”
Section: Episode 2: C16 Collides With the Drygalski Ice Tongue Causimentioning
confidence: 99%
“…The TNB polynya is a coastal polynya bounded by three steep glacier valleys, Reeves Glacier and Priestley Glacier draining into the Nansen Ice Sheet (NIS); and David Glacier terminating in the Drygalski Ice Tongue (DIT). The TNB polynya southern border is protected from incoming sea ice by the DIT, whose length controls the polynya size [Frezzotti and Mabin, 1994]. The RIS polynya forms in the lee of the floating ice shelf, and the surrounding ice shelf is relatively smooth and flat compared with the coast surrounding the TNB polynya.…”
Section: Introductionmentioning
confidence: 99%